PENGARUH FINANCIAL DISTRESS, TATA KELOLA PERUSAHAAN, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK - Yantine, Melony Nurjul; Rahayuningsih, Deasy Ariyanti (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
The purpose of this research is to examine the significance of the effect of each independent variable. The independent variables in this study are financial distress, managerial ownership, board of director size, size of independent board of commissioners, audit committee, institutional ownership, and profitability. The dependent variable in this study is tax avoidance. The objects in this study are manufacturing companies listed on Indonesia Stock Exchange (IDX) for 2019-2021. The sample was selected taking into account several criteria from manufacturing companies for the 2019-2021 period listed on the Indonesia Stock Exchange (IDX), where 42 companies met the criteria and produced 126 data as samples. The hypothesis was tested by using multiple regression analysis. The results of this study indicate that financial distress has a significance value of 0.040 with a coefficient of -0.023 and profitability has a significance value of 0.012 with a coefficient of -0.507, both of which have a positive effect on tax avoidance. Managerial ownership variable has a significance value of 0.297, board of directors size variable has a significance value of 0.972, independent board of commissioners size variable has a significance value of 0.102, audit committee variable has a significance value of 0.153, and institutional ownership variable has a significance value of 0.245, which means that the five independent variables have no effect on tax avoidance. Tax avoidance tends to be done when the company is experiencing a downturn or an increase in economic terms with the aim of optimizing the company's financial position.